WAS JUSTICE DONE? Ntamo v Minister of Safety & Security 2001 1 SA 830 (Tk); Minister of Safety & Security v Ntamo 2003 1 SA 547 (SCA) - James Grant (Obiter, 2023)
Minister of Safety and Security v Ntamo 2003 1 SA 547 SCA is a case which turned on the issue of private defence. The respondent (plaintiffs), who had succeeded in the trial court (Ntamo v Minister of Safety and Security 2001 1 SA 830 (Tk)) in a dependant‟s action, comprised the wife and children of the deceased. The deceased had been shot dead by members of the South African Police Services.The Supreme Court of Appeal (SCA) judgment (Minister of Safety and Security v Ntamo 2003 1 SA 547 (SCA)) is clearly more defensible than that of the trial court. Both judgments however require some comment: the trial court judgment for an observation of some difficulties in adjudicating upon private defence, particularly since the SCA judgment adopted a different route and did not engage with the difficulties encountered by the trial court, and as such issued no confirmation nor corrections. The SCA judgment is brief (four pages) but requires comment, briefly, on the burden of proof resting on the defendant who raises private defence.